Older patient hospital admissions following primary care referral: the truth is in the referring. (May 2016) - Scully, P.; O'Donnell, B.; Peters, C.; O'Connor, M.; Lyons, D.
Abstract Background Health information has a major role in the planning of future healthcare provision. With current reconfiguration and cost saving measures, further demands are being placed on acute hospitals. Aim To examine the elderly admissions and the referral documentation of older patients admitted to a tertiary level hospital. Methods A retrospective analysis of primary care referral documentation for all acute admissions of patients over 75 years to University Hospital Limerick (UHL) over a 2-month period. Documentation was analysed on the basis of patient demographics, presenting complaint and referral source. Primary care referral documentation was then analysed on the basis of presenting complaint, patient demographics, referrer details, and the clinical information provided. Results Over the 2-month period there were a total of 381 elderly admissions through the Emergency department. The most common presenting complaint was with shortness of breath (21.5 %). 42.5 % of admissions were from a primary care setting. 31.1 % of referrals were typed and 47.0 % handwritten. Over 90 % of referrals contained the patient's name, date of birth and address. 98.7 % of referrals included a presenting complaint and 54 % included a past medical history. 20 % of referrals listed known drug allergies, while 9.3 % documented social history or baseline functional status. Referral letters from general practice and after-hour services were largely similar. Conclusions Almost all primary care referrals included the required details as per recent HIQA guidelines. The further inclusion of optional information relating to patient social or functional status, which are of particular relevance to the older population may help patient management.